Standardization Of The Recipe For Rendang Lokan (Geliona erosa) In Lengayang District, Pesisir Selatan Regency - Efendi, Dona Andeska; Syarif, Wirnelis (Universitas Negeri Padang, 2022)
The purpose of this study was to produce the best standardization of the recipe for randang lokan (geliona erosa) in Lengayang District, Pesisir Selatan Regency to determine the ingredients and spices used, plating, processing techniques and 4 analysis of quality indicators which are expected to cover color, aroma, texture and taste. The background of the research is that there are spices used, processing techniques. Different processing techniques produce different quality indicators. This type of research is a mixed method. Sources of qualitative research data were obtained from 10 community experts in processing randang lokan (galiona erosa) and quantitative data sources were obtained from the community of 10 trained panelists who were experts in making randang lokan (galiona erosa) and 5 limited panelists from UNP Catering lecturers. Qualitative data collection techniques include observation, interviews, documentation while quantitative data collection techniques include the organoleptic test questionnaire format. Based on the results of the organoleptic test, it was found that the color quality indicators of chestnut randang lokan (geliona erosa) (brownish black), lokan aroma (galiona erosa) (fragrant spices), aroma (distinctive fragrant randang lokan), lokan texture (galiona erosa) (soft), the texture of the chestnut randang lokan (galiona erosa) (quite dry), the texture of the randang talua (quite crisp and quite brittle), the taste of lokan (galiona erosa) (not fishy), the taste of the chest randang lokan (galiona erosa) (tasty).